ASSESSING VOCATIONAL HIGH SCHOOL EFL TEACHERS’ TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE IN ONLINE LEARNING - Happy Indriyono; Markus Budiraharjo; Barli Bram (Journey: Journal of English Language and Pedagogy, 2022)
During the Covid-19 pandemic, classroom activities are mostly conducted online using Information and Communication Technology (ICT). This situation requires teachers to be literate in technology for teaching. Some pedagogical methods and platforms are available to support learning activities and a number of constraints need resolving. This study aimed to investigate the empirical data of teachers’ readiness for English education in vocational high school considering the technology integration in teaching and to uncover the obstacles. Teachers’ readiness was assessed using Mishra and Koehler’s (2006) Technological Pedagogical Content Knowledge (TPACK) framework. Descriptive quantitative research was conducted to the members of the forum of vocational high school English teachers located in Surakarta. It was predicted that a number of English teachers participating in this research were not ready for technology integration in the future in spite of their strong desire to learn the technology. Based on the participants’ responses, it was also crucial to have supports from educational institutions where teachers worked to provide relevant devices and encouraging atmosphere to enable technology-enhanced learning. It was predicted that students’ primary impediments to learning with technology were the facilities and the teacher’s pedagogical methods.